Invasion success on European coastal dunes - Silvia Giulio; Luigi Cao Pinna; Marta Carboni; Flavio Marzialetti; Alicia Teresa Rosario Acosta (Plant Sociology, 2021)
Many invasive plants are threatening the already highly vulnerable habitats of coastal dunes in Europe. Setting priority target species to control is mandatory for an effective planning of invasion management strategies at European level. This can be possible after identifying the species that currently have greater invasion success, in consideration of their ecological traits and origin. We quantified the three main components of invasion success for the extra-European alien plants found on European coastal dunes: local abundance, regional distribution and niche breadth, and related them to their life forms and origins. We found that life form was a better predictor of invasion success. In particular, geophytes and therophytes were the species with the greatest invasion success. Quite surprisingly, alien plants from Africa appeared as the group﻿ with slightly higher mean invasion success although this result was no statistically significant. We also highlighted the species deserving special attention. Among these, Xanthium orientale, Erigeron canadensis and Oenothera gr. biennis showed the widest levels of niche breadth and regional distribution, and had overall the greatest invasion success, but other species also had high levels in one of the three components of invasion success.